Autoconsciência e espírito na fenomenologia do espírito de Hegel - Almeida, Patrícia Riffel de (2014)
This dissertation presents different interpretations about the status of the subject and the Spirit in Hegel's philosophy of spirit, especially in the Phenomenology of Spirit. Are brought to the fore the Hegelian themes of the critique of intuitionism, formalism and empiricism, among others. We seek to understand the philosophy of Hegel in light of their continuities and ruptures with the idealism of Kant and Fichte, mainly. In addition, some derivations of the ontological argument for the field of moral and political action are presented.